The spatial variability of ice-jam bank morphologies along the Mistassini River (Quebec, Canada): an indicator of the ice-jam regime? - Morin, Stephanie; Boucher, Etienne; Buffin-Belanger, Thomas (Natural Hazards, 2015)
Keywords: Ouvrage_Collectif_Numéro1

Estimation of large wood budgets in a watershed and river corridor at interdecadal to interannual scales in a cold‐temperate fluvial system - Boivin, Maxime; Buffin‐Bélanger, Thomas; Piégay, Hervé (Earth Surface Processes and Landforms, 2017)
Abstract Large wood (LW) is a ubiquitous feature in rivers of forested watersheds worldwide, and its importance for river diversity has been recognized for several decades. Although the role of LW in fluvial dynamics has been extensively documented, there is a need to better quantify the most significant components of LW budgets at the river scale. The purpose of our study was to quantify each component (input, accumulation, and output) of a LW budget at the reach and watershed scales for different time periods (i.e. a 50‐year period, decadal cycle, and interannual cycle). The LW budget was quantified by measuring the volumes of LW inputs, accumulations, and outputs within river sections that were finally evacuated from the watershed. The study site included three unusually large but natural wood rafts in the delta of the Saint‐Jean River (SJR; Québec, Canada) that have accumulated all LW exported from the watershed for the last 50 years. We observed an increase in fluvial dynamics since 2004, which led to larger LW recruitment and a greater LW volume trapped in the river corridor, suggesting that the system is not in equilibrium in terms of the wood budget but is rather recovering from previous human pressures as well as adjusting to hydroclimatic changes. The results reveal the large variability in the LW budget dynamics during the 50‐year period and allow us to examine the eco‐hydromorphological trajectory that highlights key variables (discharge, erosion rates, bar surface area, sinuosity, wood mobility, and wood retention). Knowledge on the dynamics of these variables improves our understanding of the historical and future trajectories of LW dynamics and fluvial dynamics in gravel‐bed rivers. Extreme events (flood and ice‐melt) significantly contribute to LW dynamics in the SJR river system. Copyright © 2017 John Wiley & Sons, Ltd.
Keywords: Boivin_Maxime

Using tree-rings to determine large wood residence time and transport pulses in a gravel-bed river - Boivin, Maxime; Buffin-Bélanger, Thomas; Arseneault, Dominique (E3S Web of Conferences, 2018)
The Saint-Jean River (SRJ) in Eastern Canada is prone to the formation of very large rafts of wood. Managers of the SJR suspected these jams to influence salmon migration and carried out a dismantling operation to remove large wood accumulated in a 1.2 km long wood raft. This operation became a great opportunity to address key issues relating to large wood dynamics in a fluvial system: residence time and flood contribution to wood recruitment and transport. During the dismantling, we systematically sampled 319 trees from which year of death could be estimated from dendrochronology and year of accumulation in the raft could be obtained from satellite and aerial photos. These two dates allowed us to quantify the residence time for 262 datable large wood (LW) within the fluvial system, to examine the peak years of LW recruitment and to correlate the raft growth rate with hydrometeorological conditions since 1993. The results also emphasized four types of LW flood related to wood dynamics: 1) an erosive flood that produces a large amount of wood in river, 2) a mobilizing flood that carries large quantities of wood, 3) a flood mix that both recruits and transports large quantities of wood, and 4) an ice-breakup flood.
Keywords: Boivin_Maxime

Three‐dimensional turbulent structures at a medium‐sized confluence with and without an ice cover - Biron, Pascale M.; Buffin‐Bélanger, Thomas; Martel, Nancy (Earth Surface Processes and Landforms, 2019)
Abstract River confluences are characterized by a complex mixing zone with three‐dimensional (3D) turbulent structures which have been described as both streamwise‐oriented structures and Kelvin–Helmholtz (KH) vertical‐oriented structures. The latter are visible where there is a turbidity difference between the two tributaries, whereas the former are usually derived from mean velocity measurements or numerical simulations. Few field studies recorded turbulent velocity fluctuations at high frequency to investigate these structures, particularly at medium‐sized confluences where logistical constraints make it difficult to use devices such as acoustic doppler velocimeter (ADV). This study uses the ice cover present at the confluence of the Mitis and Neigette Rivers in Quebec (Canada) to obtain long‐duration, fixed measurements along the mixing zone. The confluence is also characterized by a marked turbidity difference which allows to investigate the mixing zone dynamics from drone imagery during ice‐free conditions. The aim of the study is to characterize and compare the flow structure in the mixing zone at a medium‐sized (~40 m) river confluence with and without an ice cover. Detailed 3D turbulent velocity measurements were taken under the ice along the mixing plane with an ADV through eight holes at around 20 positions on the vertical. For ice‐free conditions, drone imagery results indicate that large (KH) coherent structures are present, occupying up to 50% of the width of the parent channel. During winter, the ice cover affects velocity profiles by moving the highest velocities towards the centre of the profiles. Large turbulent structures are visible in both the streamwise and lateral velocity components. The strong correlation between these velocity components indicates that KH vortices are the dominating coherent structures in the mixing zone. A spatio‐temporal conceptual model is presented to illustrate the main differences on the 3D flow structure at the river confluence with and without the ice cover. © 2019 John Wiley & Sons, Ltd.

Dynamics of groundwater floodwaves and groundwater flood events in an alluvial aquifer - Buffin-Bélanger, Thomas; Cloutier, Claude-André; Tremblay, Catherine; Chaillou, Gwénaëlle; Larocque, Marie (2016)
In gravelly floodplains, streamflood events induce groundwater floodwaves that propagate through the alluvial aquifer. Understanding groundwater floodwave dynamics can contribute to groundwater ﬂood risk management. This study documents groundwater floodwaves on a flood event basis to fully assess environmental factors that control their propagation velocity, their amplitude and their extension in the floodplain, and examines the expression of groundwater flooding in the Matane River floodplain (Quebec, Canada). An array of 15 piezometers equipped with automated level sensors and a river stage gauge monitoring at 15-minute intervals from September 2011 to September 2014 were installed within a 0.04-km2 area of the floodplain. Cross-correlation analyses were performed between piezometric and river-level time series for 54 flood events. The results reveal that groundwater floodwave propagation occurs at all flood magnitudes. The smaller floods produced a clear groundwater floodwave through the floodplain, while the largest floods affected local groundwater flow orientation by generating an inversion of the hydraulic gradient. Propagation velocities ranging from 8 to 13 m/h, which are two to three orders of magnitude higher than groundwater velocity, were documented while the induced pulse propagated across the floodplain to more than 230 m from the channel. Propagation velocity and amplitude attenuation of the groundwater floodwaves depend both on flood event characteristics and the aquifer characteristics. Groundwater flooding events are documented at discharge below bankfull (< 0.5 Qbf). This study highlights the role of flood event hydrographs and environmental variables on groundwater floodwave properties and the complex relationship between flood event discharge and groundwater flooding. The role that groundwater floodwaves play in flood mapping and the ability of analytical solutions to reproduce them are also discussed.
MAG ID: 2280488768

Les conditions nivologiques et hydro-météorologiques propices au déclenchement des coulées de slush : L’exemple du Québec (Canada) - Hétu, Bernard; Fortin, Guillaume; Dubé, Jérôme; Boucher, Dominic; Buffin-Bélanger, Thomas; Gagnon, Jean-Pierre (2016)
Une coulee de slush (bouillie de neige fondante) est un ecoulement rapide constitue d’un melange de neige fondante, d’eau, de boue et de debris de toutes sortes. Les sept sites analyses demontrent que les coulees de slush peuvent survenir dans des contextes topographiques fort differents qui presentent toutefois des similitudes au niveau du mode d’enneigement et des conditions hydro-meteorologiques. Les coulees de slush etudiees demarrent dans des ruisseaux d’ordre 1 ou 2, etroits et peu profonds, de pente tres variable (de 1° a plus de 30°), qui sont combles par des bouchons de neige dense soufflee par le vent ou transportee par les avalanches. Parce qu’ils s’opposent a la libre circulation des eaux de fusion lors des periodes de fonte acceleree, ces bouchons de neige favorisent la saturation du manteau neigeux jusqu’a la rupture sous l’effet combine de la pression hydrostatique et de la gravite. Les onze coulees analysees, qui se sont produites entre 1936 et 2013, permettent de definir deux scenarios hydro-meteorologiques propices a leur declenchement : 1) des redoux de longue duree caracterises par des temperatures qui restent positives pendant plusieurs jours consecutifs sans apport de precipitations liquides; 2) des redoux relativement courts (moins de 48 heures) couples a des precipitations liquides abondantes. Largement meconnues au Quebec, les coulees de slush pourraient etre plus frequentes a l’avenir en reponse au rechauffement climatique en cours.
MAG ID: 2589734161